Competitiveness: A Strategic Resource-Based Approach To Business Management - Arias Hancco, Jeymi Fabiola (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Competitiveness is fundamental for the growth of a country’s economic sectors, and its analysis and evaluation should start at a microeconomic level, so this study aimed to determine the influence of strategic business management resources on competitiveness. The methodology used corresponds to a basic study, with a descriptive, explanatory and correlational cross-sectional design, using a census of 127 mypes in the agro-export sector of the Tacna Region, Peru. The main results conclude that strategic business management resources have a significant influence on competitiveness.